Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\text{Đặt }x^2=m\ge0;y^2=n\ge0\Rightarrow m+n=1\)
\(\text{Ta có: }\frac{m^2}{a}+\frac{n^2}{b}=\frac{\left(m+n\right)^2}{a+b}\Leftrightarrow\left(a+b\right)\left(\frac{m^2}{a}+\frac{n^2}{b}\right)=\left(m+n\right)^2\left(\text{BĐT Bunhiacopki}\right)\)\(\Leftrightarrow m^2+n^2+\frac{b}{a}m^2+\frac{a}{b}n^2=m^2+n^2+2mn\)
\(\Leftrightarrow\frac{b}{a}m^2+\frac{a}{b}n^2-2mn=0\left(1\right)\)
\(\text{+Nếu }\frac{a}{b}< 0\text{ thì (1)}\Leftrightarrow-\left(\sqrt{-\frac{b}{a}m}\right)^2-2mn-\left(\sqrt{-\frac{a}{b}n}\right)^2=0\Leftrightarrow\left(\sqrt{-\frac{b}{a}m}+\sqrt{-\frac{a}{b}n}\right)^2=0\)
\(\Leftrightarrow\sqrt{-\frac{b}{a}m}+\sqrt{-\frac{a}{b}n}=0\Leftrightarrow m=n=0\left(\text{loại}\right)\)
\(\text{Xét }\frac{a}{b}>0;\left(1\right)\Leftrightarrow\left(\sqrt{\frac{b}{a}m}\right)^2-2mn+\left(\sqrt{\frac{a}{b}n}\right)^2=0\)
\(\Leftrightarrow\left(\sqrt{-\frac{b}{a}m}-\sqrt{-\frac{a}{b}n}\right)^2=0\Leftrightarrow\sqrt{\frac{b}{a}m}=\sqrt{\frac{a}{b}n}\)
\(\Leftrightarrow bm=an\Leftrightarrow bx^2=ay^2\left(a,b>0\right)\)
\(\Rightarrow\frac{x^2}{a}=\frac{y^2}{b}=\frac{x^2+y^2}{a+b}=\frac{1}{a+b}\)
\(\frac{x^{2006}}{a^{1003}}+\frac{y^{2006}}{b^{1003}}=\left(\frac{x^2}{a}\right)^{1003}+\left(\frac{y^2}{b}\right)^{1003}=\frac{1}{\left(a+b\right)^{1003}}+\frac{1}{\left(a+b\right)^{1003}}=\frac{2}{\left(a+b\right)^{1003}}\left(đpcm\right)\)
1/ Ta có: \(\frac{x^4}{1a}+\frac{y^4}{b}=\frac{\left(x^2+y^2\right)^2}{a+b}\)
\(\Leftrightarrow1bx^4\left(a+b\right)+ay^4\left(a+b\right)=ab\left(x^4+2x^2y^2+y^4\right)\)
\(\Leftrightarrow\left(ay^2-bx^2\right)^2=0\)
\(\Rightarrow\frac{x^2}{1a}=\frac{y^2}{b}=\frac{\left(x^2+y^2\right)}{a+b}=\frac{1}{a+b}\)
\(\Rightarrow\frac{x^{2006}}{1a^{1003}}=\frac{y^{2006}}{b^{1003}}=\frac{1}{\left(a+b\right)^{1003}}\)
\(\Rightarrow\frac{x^{2006}}{a^{1003}}+\frac{y^{2006}}{b^{1003}}=\frac{2}{\left(a+b\right)^{1003}}\)
Sửa đề \(M=\left(1+\frac{a}{b}\right)\left(1+\frac{b}{c}\right)\left(1+\frac{c}{a}\right)\)
Ta có: \(a^3+b^3+c^3=3ab\)
\(\Leftrightarrow\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ca\right)=0\)
\(\Rightarrow\orbr{\begin{cases}a+b+c=0\\a^2+b^2+c^2-ab-bc-ca=0\end{cases}}\)
TH1: a+b+c=0
=> \(\hept{\begin{cases}a=-\left(b+c\right)\\b=-\left(a+c\right)\\c=-\left(a+b\right)\end{cases}}\)
Thay vào M ta được M=\(\left(1-\frac{b+c}{b}\right)\left(1-\frac{a+c}{c}\right)\left(1-\frac{a+b}{a}\right)\)
\(\Rightarrow M=\frac{-c}{b}\cdot\frac{-a}{c}\cdot\frac{-b}{a}=-1\)
TH2: \(a^2+b^2+c^2-ab-bc-ca=0\)
\(\Leftrightarrow\left(a-b\right)^2+\left(b-c\right)^2+\left(c-a\right)^2=0\)
\(\Rightarrow M=\left(1+1\right)\left(1+1\right)\left(1+1\right)=8\)
a) Ta có:
\(n\left(2n-3\right)-2n\left(n+1\right)\)
\(=2n^2-3n-2n^2-2n\)
\(=-5n\)
Vì \(-5n⋮5\) với n thuộc Z
\(\Rightarrow n\left(2n-3\right)-2n\left(n+1\right)⋮5\) với n thuộc Z
b) Ta có:
\(\left(n^2+3n-1\right)\left(n+2\right)-n^3+2\)
\(=n^3+3n^2-n+2n^2+6n-2-n^3+2\)
\(=5n^2+5n\)
\(=5\left(n^2+n\right)\)
Vì \(5\left(n^2+n\right)⋮5\)
\(\Rightarrow\left(n^2+3n-1\right)\left(n+2\right)-n^3+2⋮5\)
c) Ta có:
\(\left(xy-1\right)\left(x^{2003}+y^{2003}\right)-\left(xy+1\right)\left(x^{2003}-y^{2003}\right)\)
\(=\left(xy+1-2\right)\left(x^{2003}+y^{2003}\right)-\left(xy+1\right)\left(x^{2003}-y^{2003}\right)\)
\(=\left(xy+1\right)\left(x^{2003}+y^{2003}\right)-2\left(x^{2003}+y^{2003}\right)-\left(xy+1\right)\left(x^{2003}-y^{2003}\right)\)
\(=\left(xy+1\right)\left(x^{2003}+y^{2003}-x^{2003}+y^{2003}\right)-2\left(x^{2003}+y^{2003}\right)\)
\(=2\left(xy+1\right)y^{2003}-2\left(x^{2003}+y^{2003}\right)\)
Vì \(2\left(xy+1\right)y^{2003}⋮2\)
\(2\left(x^{2003}+y^{2003}\right)⋮2\)
\(\Rightarrow2\left(xy+1\right)y^{2003}-2\left(x^{2003}+y^{2003}\right)⋮2\)
\(\Rightarrow\left(xy-1\right)\left(x^{2003}+y^{2003}\right)-\left(xy+1\right)\left(x^{2003}-y^{2003}\right)⋮2\)